Titânio via foliar no metabolismo, absorção de nutrientes e produtividade de batata - Bacilieri, Fernando Simoni (2015)
The potato (Solanum tuberosum L.) has great importance in human nutrition where it occupies the fourth place among the most consumed foods in the world. It is a highly demanding culture technology especially in the nutritional point of view. Despite the titanium (Ti) is not considered a nutrient, studies have shown beneficial effects of this element when applied to plants. The application of Ti leaf can be an alternative for this element is slightly movable in the soil and is generally present in insoluble forms. Thus, the objective was to evaluate the influence of application rates of Ti foliar in the potato crop. We conducted an experiment in the period from August to November 2014, installed at the experimental station Udi Pesquisa e Development in Uberlândia-MG, with kind Ágata. Variables related to metabolism were evaluated: SPAD chlorophyll content, nitrate reductase activity (NRA), lipid peroxidation (LP), urease, proline, catalase (CAT), superoxide dismutase (SOD) and peroxidase (POD). Nutritional factors such as levels of nutrients nitrogen (N), copper (Cu), iron (Fe), manganese (Mn) and zinc (Zn) present in leaves and tubers were measured stages of growth, tuber and tuber filling. At the end of the crop cycle was quantified the average mass, diameter, commercial classification and productivity of tubers. The design was a randomized block design with four replications and six treatments. The supply of the Ti compound fertilizer was through for 5% of magnesium oxide, 10% sulfur trioxide and 0,85% titanium complex and the treatments was: T1 - without the application of Ti, T2 -10.2; T3 - 15.3; T4 - 20.4; T5 - 22.9 and T6 - 25.5 g Ti ha-1 divided into three equal applications during the growth phase, tuber and tuber filling. It was concluded that in the growth phase the foliar application of Ti reduces the Mn content in the leaves and there is increased activity of POD and ANR and reduced urease activity. In the tuberization phase the Fe absorption, SOD activity and POD response to increasing Ti dose. In tubers filling stage foliar application of Ti increases chlorophyll levels (Spad value). The application of Ti in the leaf growth stages, tuber and tuber filler results in a lower Zn content in the tubers. The average tuber weight, the average diameter of tubers and the total productivity of tubers are affected by foliar application of Ti. The dose Ti foliar applied for further tuber yield is 5.74 g Ti ha-1.